Efficiency of Conventional Vs Islamic Banks in Indonesia: Pre and Mid-Covid Analysis - Fikar Adiaksa; Teguh Santoso (Economics Development Analysis Journal, 2025)
This study aims to assess the technical efficiency of Indonesia’s conventional and Islamic banks and to examine whether their efficiencies differ between the periods before and during the COVID-19 pandemic. Bank input and output data are obtained from financial statements sourced from the CEIC Global Database for 96 Indonesian banks over the period from 2015 to 2022. The study employs bootstrap Data Envelopment Analysis (DEA) under both production and intermediation approaches to estimate bias-corrected technical efficiency. Independent t-tests are conducted to compare efficiency scores between conventional and Islamic banks, as well as to examine differences in technical efficiency before versus during the COVID-19 pandemic. The empirical findings indicate that Indonesian banks during the pandemic period were generally less efficient than before, and Islamic banks consistently exhibited lower technical efficiency than conventional banks. Although conventional banks outperform Islamic ones overall, the efficiency gap is not statistically significant during the pandemic. Moreover, banks show higher efficiency under the production approach, indicating stronger performance in revenue generation than fund intermediation. This study advises Indonesian banks to increase interest income (or fund disbursements, for Islamic banks), non-interest income, and loans while also considering risk to improve overall technical efficiency.